Contamination of public parks and squares from Guarulhos (São Paulo State, Brazil ) by Toxocara spp. and Ancylostoma spp. - Marques, Jacó Pereira; Guimarães, Catarina de Rezende; Boas, Ailton Vilas; Carnaúba, Paulo Usignolo; Moraes, Josué de (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
The contaminated soil with mammal feces is an important factor of risk to infection with zoonotic diseases. Amongst these zoonoses are visceral larva migrans and cutaneous larva migrans caused by Toxocara spp. and Ancylostoma spp., respectively. The aim of this study was to assess the environmental contamination by Toxocara spp. eggs and hookworms (Ancylostoma spp.) in public parks and squares in the city of Guarulhos, a metropolitan area of São Paulo, São Paulo State, Brazil. Soil samples were collected, between September and December 2010, and examined using the centrifugal flotation technique with sodium dichromate and zinc sulphate as well as the modified Baermann method. Notably, 35 (74.5%) of the 47 districts surveyed in Guarulhos possessed samples contaminated with Toxocara spp. and/or eggs or larvae of Ancylostoma spp. The frequency of Toxocara spp. and Ancylostoma spp. in the samples from public areas was 68.1% and 46.8%, respectively. Overall, the eastern side of Guarulhos is the region with the highest occurrence of causative agents of larva migrans. In all collection sites, the presence of feces from dogs and cats accompanied by their owners and stray animals were observed. Notably, it is important to adopt measures to control dog and cat breeding, to treat infected animals, and provide health education to the population.